World Development - list of contents and author index (New York : Pergamon prss, 1985)
The ephemera collection contains documents of everyday life generally covering publications of fewer than five pages. These may include: advertising material, area guides, booklets, brochures, samples of merchandise postcards, posters, programs, stickers and tickets.
Action for World Development was an Australian interdenominational initiative to promote world development. It began with the establishment of the Joint Secretariat for World Development, which set up and ran a study program in 1972.